Pengaruh Pengetahuan dan Perilaku Petani dalam Pengendalian Hama Tikus terhadap Produktivitas Usaha Tani Padi di Desa Mojolegi, Teras, Boyolali - Muhammad Andriyanto; Hari Purwanto; Unna Ria Safitri; Tien Suhartini (Pusat Riset dan Inovasi Nasional, 2026)
This study attempts to examine how farmers' knowledge and behavior regarding rat control affect rice yields in Mojolegi Village, Teras, Boyolali. This study applies a quantitative approach by selecting 53 farmers as samples through a simple random sampling technique. Data collection was conducted using a questionnaire using a Likert scale and analyzed through multiple linear regression using SPSS software. The findings of this study indicate that farmers' knowledge has no significant effect on rice yields (t = -0.535; sig. = 0.595), while attitudes have a positive and significant effect (t = 3.609; sig. <0.001). The results show that farmers' behavior and knowledge have a significant effect on rice farming productivity (F = 27.190; sig. = <0.001). These two variables contribute 52.1% of the variation in rice farming productivity, according to the R2 value of 0.521. Other factors not included in this study contribute 47.9% of the variation. In addition, it was found that farmer behavior plays a more significant role in increasing rice farming productivity.